The reality of sonography of the infant hip in Brazil: results and recommendations - Giovanna Galvão Braga Motta; Natasha Vogel Majewski Rodrigues; Susana Reis Braga; Márcio Luís Duarte; Patricia Moreno Grangeiro; Alexandre Francisco de Lourenço (Exploration of Musculoskeletal Diseases)
Since 1980, when Professor Reinhard Graf developed a novel technique, sonography of the infant hip has played a prominent role in the early diagnosis of developmental dysplasia of the hip (DDH). Brazil is a vast country, and disparities exist among regions and between the public and private health systems. In addition, healthcare professionals often have limited knowledge of DDH, and patients need to be referred to larger urban centers for definitive diagnosis and appropriate treatment. These reasons, and more, may hinder the early diagnosis of DDH. Following the successful implementation of similar neonatal screening programs for other conditions in Brazil, developing a screening program for DDH in Brazil is imperative. Such a program should consider training professionals to use Graf’s technique as a diagnostic procedure. It is recommended that more studies be conducted in every region of the country to provide a broader understanding of the current role of sonography in the screening and diagnosis of DDH in infants in Brazil.